Analisis Vegetasi Dasar di Bawah Tegakan Jati Emas (Tectona grandis L.) dan Jati Putih (Gmelina arborea Roxb.) di Kampus Universitas Andalas - Indah Asmayannur; - Chairul; Zuhri Syam (Universitas Andalas, 2012)
The analysis of understory vegetation on Jati Emas (Tectona grandis L.) and Jati Putih (Gmelina arborea Roxb.) stand in Andalas University campus was conducted from May until July 2012. The objectives of this research were: to determine species composition, structure and diversity index of species. The method of this research was quadratic method with line 1 m x 1 m. The results were found 22 families, 43 species and 624 individuals. The highest importance value was dominated by Gleichenia linearis (29.7%) at Jati Emas Stand and Melastoma malabathricum (38.19%) at Jati Putih Stand. Diversity index (H’) had value were 2.88, 2.81, 2.46 and it’s categorizhed as middle diversity. The higher simillarity index was found between Jati Emas and Jati Putih stand (40.74%), next between Jati Emas and without Jati stand (24%) was found as middle simillarity index and the lower similliarity index was found between Jati Putih and without Jati stand (13.04%).Keywords: Understory, Tectona grandis, Gmelina arborea